Total, bioavailable and free 25-hydroxyvitamin D levels as functional indicators for bone parameters in healthy children. - You Joung Heo (Public Library of Science (PLoS), 2021)
Objectives Vitamin D is essential for bone health. Not only total but also free 25-hydroxyvitamin D (25OHD) may contribute to bone mass. We sought to determine which vitamin D measure best reflected clinical and bone parameters in healthy children. Methods A cross-sectional study including 146 healthy children (71 boys, 9.5 ± 1.9 years) conducted at a tertiary medical center. We used a multiplex liquid chromatography-tandem mass spectrometry-based assay to simultaneously measure vitamin D metabolites. The bioavailable and free 25OHD (25OHDBioA and 25OHDFree) levels were calculated using the genotype-specific or genotype-constant affinity coefficients of vitamin D-binding proteins (yielding spe-25OHDBioA, spe-25OHDFree and con-25OHDBioA, con-25OHDFree respectively). The 25OHDFree level was directly measured (m-25OHDFree). Bone mineral content (BMC) and bone mineral density (BMD) were assessed via dual-energy X-ray absorptiometry. Results The total 25OHD (25OHDTotal), the two forms of 25OHDBioA, the three forms of 25OHDFree, and 24,25-dihydroxyvitamin D3 levels correlated with parathyroid hormone level (all p < 0.01). Serum 25OHDTotal and m-25OHDFree levels were influenced by age, pubertal status, season, body mass index (BMI), daylight hours, and vitamin D intake (all p < 0.05). The con-25OHDBioA and con-25OHDFree levels better reflected pubertal status and daylight hours than did the spe-25OHDBioA and spe-25OHDFree levels (both p < 0.01). The association between the 25OHDTotal level and bone parameters varied according to the BMI (interaction p < 0.05). In 109 normal-weight children, the con-25OHDBioA and con-25OHDFree levels correlated with total body BMC and BMD (both p < 0.05), whereas the 25OHDTotal and 24,25-dihydroxyvitamin D3 levels were associated with total body BMC (both p < 0.05). No such association was found in overweight or obese children. Conclusions In healthy children, total, bioavailable, and free 25OHD levels comparably reflected lifestyle factors. In normal-weight children, the con-25OHDBioA and con-25OHDFree, but not m-25OHDFree levels, reflected bone mass, as did the 25OHDTotal level.